Junior High School Student Career Orientation: Congruence between the Selection of School Majors and Self-Potential - Abdillah, Muhamad Hasan; Zahra, Zahra; Delvani, Rina; Mulyanti, Nasywa Dewi (UI Scholars Hub, 2025)
This study aims to identify the level of career orientation of junior high school students as a first step in providing career interventions. The subjects in this study were junior high school students from class IX in Samarinda City, comprising three schools with 69 students. The sample selection was obtained using a stratified random sampling technique. Researchers use the career orientation scale as the research instrument, whereas the data analysis technique uses descriptive analysis and an independent t-test. The descriptive analysis results show that the career orientation level of junior high school students in Samarinda City tends to be low. The independent t-test analysis results between the three schools show no difference in the level of student career orientation (F = 0.13 and p = 0.875). Therefore, low levels of student career orientation tend to be experienced by all schools (group A, group B, and group C). Thus, the schools should socialize on the importance of career planning from the junior high school level so students can choose school majors in high school according to their potential.